The Influence of Job Training, Work Discipline, and Communication on Employee Performance - Setyorini, Izni Nadah; Subarjo (Economic and Business Horizon, 2025)
Employee performance is influenced by various factors, including job training, work discipline, and communication. This study aims to examine the effects of these factors on employee performance. A quantitative approach with an associative design was employed, involving 35 employees selected using a saturated sampling technique. Data were collected through an online questionnaire using a Likert scale. Analysis included validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and the coefficient of determination. The results show that job training does not have a significant effect on performance (p = 0.790), while work discipline (p = 0.044) and communication (p = 0.018) have positive and significant effects. Additionally, the F-test indicates that the three variables together significantly influence employee performance. The coefficient of determination suggests that other factors not examined may also play a role.  The findings emphasize that work discipline and effective communication are key to improving employee performance, whereas job training requires further evaluation to maximize its impact.